Research on the Coating Method of TiO2 Nanotubes on Quartz Tubes and Investigate the Ethanol Degradation - Khanh, Tran Duc; Giang, Vu Ha; Huong, Trinh Thi Phong; Luan, Vu Thanh; Lan, Nguyen Thi; Thuy, Dao Thi Thu; Anh, Le Tuan; Dong, Pham Thanh; Chau, Nguyen Thi Minh; Oanh, Le Thi Hoang; Ha, Hoang Van (VNU Journal of Science: Natural Sciences and Technology, 2021)
Titanium dioxide (TiO 2 ) is widely applied in the field of pollution treatment due to its good catalytic properties and being an environmentally friendly material. In this study, TiO 2 nanotubes were prepared from commercial TiO 2 particles. The effects of carboxymethyl cellulose (CMC) and liquid glass (sodium silicate) on catalyst activity and catalyst adhesion on quartz tubes were investigated. Transmission microscopy (TEM), scanning microscope (SEM), X-ray diffraction (XRD), X-ray energy dispersive spectroscopy, Fourier transform infrared spectroscopy (FT-IR) were used for the characterization of the catalyst. In this study, the ethanol degradation ability of the catalyst, which was added with 0; 0.5; 1, and 1.5% liquid glass and calcined at 400 and 500 o C, was determined. TiO 2 nanotubes after preparation have a uniform diameter from 10-12 nm and an average length of about 150nm, specific surface area increases markedly compared to commercial granules (nearly 15 times). The results showed that CMC plays an important role in the thickness and distribution of TiO 2 on the quartz surface. Liquid glass significantly affects the ethanol degradation efficiency.